Strategic environmental assessment-A tool for sustainable development - Agrawal, Pooja; Agrawal, Anita (Recent Research in Science and Technology, 2013)
Strategic Environmental Assessment (SEA) is the environmental assessment of policies, plans and programmes. It came in practice as an improvement over the Environmental Impact Assessment (EIA) to assist in sound environmental decision-making. It integrates the socioeconomic values with the environmentally viable development for better decision making. The scope of SEA is pluralistic, diversified, multidisciplinary and inter-sectorial. Infrastructure development is the main activities of development for any nation. These days Highway infrastructure development is the concern of main focus in India. This paper describes the concept of SEA; the evolution of SEA; the relation between SEA and ElA; SEA and sustainability criteria; the benefits of SEA; and the general methodology to perform SEA, which can be adopted for the highway infrastructure projects for sustainable development. <!--EndFragment--> aï¿½ï¿½ -oØ‡F `oF margin-bottom:.0001pt; text-align:left;text-indent:0in;mso-char-indent-count:0'>Asso. Prof. & Head, Dept of Chemistry, RITEE, Raipur, India.